Diagnostic Value of Contrast-Enhanced Magnetic Resonance Vessel Wall Imaging on the Onset Type of Vertebral Artery Dissection - Saito, Atsushi; Fujimura, Miki; Endo, Hidenori; Omodaka, Shunsuke; Kanoke, Atsushi; Sato, Kenichi; Tominaga, Teiji (Cerebrovascular diseases (Basel, Switzerland), 2019)
Circumferential enhancement along the aneurysm wall (CEAW) by magnetic resonance (MR) vessel wall imaging has been reported to be a useful indicator for the biological activity of intracranial aneurysms such as growth and rupture. However, the significance of CEAW in vertebral artery dissection (VAD) has not been examined in detail. We quantitatively analyzed CEAW on VAD focusing on the differences in the clinical onset type. The subjects were 37 patients diagnosed with VAD who were evaluated by MR imaging in the acute phase of onset between January 2014 and May 2019. The clinical onset of VAD was categorized into 3 subtypes: (1) incidentally detected (incidental group), (2) sudden headache without cerebral ischemia and/or intracranial hemorrhage (headache group), and (3) hemorrhagic onset (hemorrhage group). Three-dimensional T1-weighted fast spin echo sequences were obtained before and after contrast material injection, and the contrast ratio (CR) of the aneurysm wall against the pituitary stalk was calculated as the indicator of CEAW. The CR values of VAD in the hemorrhage group were significantly higher than those in the headache group (0.95 vs. 0.65, p < 0.05), and the headache group had significantly higher CR values than the incidental group (0.65 vs. 0.56, p < 0.05). On receiver operating characteristic curve analysis, the optimal cutoff value of CR to distinguish the hemorrhage group from the headache group was 0.83 and that to distinguish the headache group from the incidental group was 0.61. The extent of CEAW precisely reflected the deleterious impact of VAD in the acute stage, including hemorrhagic presentation. The predictive value of CEAW for the prognosis of unruptured VAD should be evaluated in future studies.